2017
DOI: 10.26913/80s02017.0111.0012
|View full text |Cite
|
Sign up to set email alerts
|

Spectres of Ambiguity in Divergent Thinking and Perceptual Switching

Abstract: Divergent thinking as a creative ability and perceptual switching between different interpretations of an unchanging stimulus (known as perceptual multistability) are thought to rely on similar processes. In the current study, we investigate to what extent task instructions and inherent stimulus characteristics influence participants' responses. In the first experiment, participants were asked to give as many interpretations for six images as possible. In the second experiment, participants reported which of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Studies have focused on personality traits, previous experiences, attention, and executive functioning as individual difference factors related to creative performance [ 16 18 ]. Educational interventions, mindset prior to creative tasks, and the influence of specific instructions given to participants have all been explored as ways to improve creative performance [ 10 , 16 ]. Divergent thinking tasks offer a valuable–but not frequently adopted–method to quantitatively assess training-related changes in creative thinking [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have focused on personality traits, previous experiences, attention, and executive functioning as individual difference factors related to creative performance [ 16 18 ]. Educational interventions, mindset prior to creative tasks, and the influence of specific instructions given to participants have all been explored as ways to improve creative performance [ 10 , 16 ]. Divergent thinking tasks offer a valuable–but not frequently adopted–method to quantitatively assess training-related changes in creative thinking [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual reversals, that is, the changes between the percepts of a bistable image, are supposed to have a correlation with the flexibility implied in creativity (Taranu & Loesche, 2017). This statement is supported by the fact that individual's creative capacity is related to their ability to think divergently, to be open to new experiences (McCrae, 1987).…”
Section: Perceptual Reversals and Insightfulnessmentioning
confidence: 98%
“…Given that divergent thinking implies jumping from one perspective to another to find logical alternatives relative to the usual way of understanding a problem (Romo, 1986), this way of thinking also implies changes in perspectives, a fact that also occurs when observers make perceptual leaps when they look at visual stimuli (Rodríguez, 2016). With this regard, it has been shown that there are correlations between the ability to do perceptual reversals and the perceptual and cognitive flexibility involved in the use of divergent thinking (Taranu & Loesche, 2017).…”
Section: Perceptual Reversals and Insightfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In marked contrast, the question of how and why one's ability to flexibly and variedly perceptually interpret ambiguous images is associated with creative thinking and imagination has been less extensively and only more sporadically explored. Despite clear historical claims and evolving practices of artists and designers (da Vinci, 1956(da Vinci, /1651Kauffman, 2019;Robert, 2008) and some early empirical intimations linking flexibility of perceptual interpretation to a corresponding flexibility and exploratory reach in the processes of creative ideation (Bergum & Bergum, 1979;Klintman, 1984), only a handful of empirical studies have examined this connection (e.g., Blake & Palmisano, 2021;Doherty & Mair, 2012;Taranu & Loesche, 2017;Wiseman et al, 2011), and have not always found support for a positive correlation (e.g., Denham et al, 2018). Additionally, these studies have often relied on bistable stimuli that allow for only two or a few alternative interpretations (Blake & Palmisano, 2021;Riquelme, 2002;Wiseman et al, 2011;X.…”
mentioning
confidence: 99%